Preparation method of novel bamboo-based hard carbon material
Through the preparation method of new bamboo-based hard carbon materials, including alkali treatment pore formation, pickling and drying, and resin coating, the problems of low specific capacity of hard carbon materials and the first Coulomb efficiency are solved, and the performance of sodium ion batteries is improved.
Patent Information
- Application Number
- CN202411708591.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing hard carbon materials as the negative electrode materials of sodium ion batteries have problems such as low specific capacity and low first-time Coulomb efficiency, and common coating methods cannot effectively improve these disadvantages.
A new method of bamboo-based hard carbon material preparation includes crushing, drying, first carbonization, crushing, alkali treatment pore making, pickling drying, resin coating and second carbonization, etc., through resin coating and Technical means such as pickling and drying to improve the specific capacity of the material and the efficiency of the first Coulomb.
The specific capacity of hard carbon materials has been improved and the first Coulomb efficiency has been improved, meeting or exceeding industry standards, and the common alkaline activators have been eliminated, the phenomenon of carbonization into ash has been avoided, and the purity and electrochemical performance of the material have been improved. .
Smart Images

Figure CN119191275A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery negative electrode materials, and in particular relates to a method for preparing a novel bamboo-based hard carbon material. Background Art
[0002] The commonly used negative electrode material for sodium-ion batteries is hard carbon, which has neither the disadvantage of graphite's difficulty in storing sodium nor the problem of soft carbon's low sodium storage capacity. It is generally believed that the basic advantages of hard carbon as a negative electrode material for sodium-ion batteries are its wide source, sufficient interlayer spacing, and small volume expansion. However, hard carbon also has relative disadvantages, such as relatively low specific capacity and relatively low first coulombic efficiency.
[0003] On the other hand, the hard carbon negative electrode used in sodium ion batteries is mainly sourced from various biomass materials, such as bamboo, reeds, and straw. The process of converting the above biomass materials into hard carbon negative electrode materials is the preparation method of hard carbon negative electrode materials, and the main purpose of the preparation method is to fully improve the above-mentioned shortcomings of hard carbon.
[0004] For example, a Chinese invention patent application with application publication number CN118738387A and application publication date 2024.10.01 discloses a method for preparing an asphalt-coated space Phragmites australis hard carbon sodium negative electrode material, in which the asphalt is coated on the outside of the space Phragmites australis hard carbon material, and the mass ratio of the asphalt to the space Phragmites australis hard carbon material is 1: (3-9).
[0005] The advantages of the asphalt-coated space reed hard carbon sodium negative electrode material applied for in this invention patent are mainly low raw material cost, simple method, short process, low energy consumption, and easy mass production.
[0006] However, the above-mentioned asphalt-coated space reed hard carbon sodium negative electrode material still has at least the following shortcomings in actual use: It is far from enough to achieve the purpose of hard carbon surface modification only through relatively common coating methods. This is reflected in the battery performance corresponding to the negative electrode material. The first coulombic efficiency is relatively low and cannot reach the industry standard of ≥88%. Summary of the invention
[0007] The present invention provides a novel method for preparing a bamboo-based hard carbon material, and the technical problem to be solved is: how to achieve a larger specific capacity and a higher first coulombic efficiency on a bamboo-based coated hard carbon material.
[0008] The technical solution adopted by the present invention to solve the above problems is: a novel method for preparing bamboo-based hard carbon material, which comprises the following steps in sequence: S1. Crushing: Add bamboo material into the crusher and perform crushing operation to obtain coarse material with a particle size of 1-3 mm; S2, drying: adding the coarse material into a dryer, performing heating and drying operations to obtain dry material; S3, first carbonization: adding the dry material into a high temperature furnace, and performing a carbonization operation in an inert gas atmosphere to obtain a precursor; S4, crushing: adding the precursor into a high-pressure crusher, and crushing the precursor to obtain a crushed material with a D50 of 7-8 μm; S5, pore-forming by alkali treatment: adding the crushed material into a mixed alkali solution and stirring to obtain a pore-forming material; S6, acid washing and drying: adding the pore-forming material to the acid solution, stirring, filtering, and drying in sequence to obtain a pure material; S7, resin coating: adding the pure material and the resin coated material into a coating machine, performing heating and stirring operations in an inert gas atmosphere to obtain a modified hard carbon material; S8, second carbonization: adding the modified hard carbon material into a high temperature furnace, and performing a carbonization operation in an inert gas atmosphere to obtain a secondary carbonized material; S9, screening: adding the secondary carbonized material to a vibrating screen and performing screening treatment, and the screened material is the final novel bamboo-based hard carbon material.
[0009] A further preferred technical solution is that in S5, the mixed alkaline solution is a deionized water mixture of potassium hydroxide and sodium hydroxide, and the OH - The concentration is 1.0-1.5 mol / L, and the weight ratio of the mixed alkali solution to the crushed material is (1.5-3.0):1.
[0010] A further preferred technical solution is that in S7, the resin coating material is any one of phenolic resin and epoxy resin, the weight ratio of the resin coating material to the pure material is (0.20-0.25):1, and the temperature of the heating and stirring operation is 250-500°C.
[0011] A further preferred technical solution is that in S2, the temperature of the heating and drying operation is 200-300°C and the time is 1-2h.
[0012] A further preferred technical solution is that in S3, the temperature of the first carbonization operation is 400-500°C, the heating rate is 2-5°C / min, and the carbonization time is 2-3h.
[0013] A further preferred technical solution is that in S6, the acid solution is a mixture of hypochlorous acid and hydrofluoric acid, the stirring and acid washing time is ≥3h, and the pH value of the filter material after filtration is ≤3.
[0014] A further preferred technical solution is that the drying operation in S6 is continued until the moisture content of the dried material is ≤0.22%.
[0015] A further preferred technical solution is that in S8, the temperature of the second carbonization operation is 850-900°C and the time is 25-30h.
[0016] A further preferred technical solution is that in S9, the mesh number of the vibrating screen is ≥ 600 meshes.
[0017] A further preferred technical solution is that in S9, the secondary carbonized material is first demagnetized before being added to the vibrating screen.
[0018] The beneficial effects of the present invention include at least: First, in the resin coating step, only the resin coating material is used without adding any of the commonly used alkaline activators. This means that in the second carbonization step, the alkaline activator will not be carbonized into ash. The direct advantage of this method is to improve the purity and electrochemical performance of the secondary carbonized material, and ultimately make the sodium ion battery corresponding to the negative electrode material have a larger specific capacity and a higher first coulombic efficiency. Second, in the resin coating step, the problem of poor modification effect and poor activation effect caused by omitting the conventional activator has been addressed in the alkali treatment pore-forming step. The above-mentioned pore-forming step can fully and appropriately increase the specific surface area of the crushed material, and finally make the resin coating effect have no obvious problems of insufficient modification and insufficient activation, which can be reflected in the final sodium ion battery performance test; Third, the acid washing and drying step can not only remove the ash on the crushed material, but also neutralize the excess alkali solution in the previous alkali treatment pore-forming step, and also wash away the inorganic salts produced by the neutralization reaction to avoid the residual inorganic substances from becoming harmful ash in the subsequent carbonization process. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a microstructure photograph of the crushed material in Example 1 of the present invention.
[0020] Figure 2 This is an enlarged photograph of the crushed material in Example 1 of the present invention.
[0021] Figure 3 This is a microstructure photograph of the modified hard carbon material in Example 1 of the present invention.
[0022] Figure 4 This is an enlarged photograph of the modified hard carbon material in Example 1 of the present invention.
[0023] Figure 5This is a microstructure photograph of the final novel bamboo-based hard carbon material in Example 1 of the present invention.
[0024] Figure 6 This is an enlarged photograph of the final novel bamboo-based hard carbon material in Example 1 of the present invention.
[0025] Figure 7 This is a specific capacity-potential relationship diagram of the sodium ion battery corresponding to the hard carbon negative electrode material in Example 1 of the present invention. DETAILED DESCRIPTION
[0026] The following descriptions are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention.
[0027] Example 1 A novel method for preparing bamboo-based hard carbon material comprises the following steps in sequence: S1, crushing: adding bamboo material into a crusher, and crushing the material to obtain coarse material with a particle size of 1-3 mm, wherein the bamboo material is selected from moso bamboo grown for more than 3 years; S2, drying: adding the coarse material into a dryer, performing a heating and drying operation to obtain a dry material, wherein the heating and drying operation is performed at a temperature of 240° C. for 2 hours, so as to improve the efficiency of the subsequent carbonization process; S3, first carbonization: adding the dry material into a high temperature furnace, and performing a carbonization operation in an inert gas atmosphere to obtain a precursor, wherein the carbonization operation temperature is 450° C., the heating rate is 3.5-5.0° C. / min, and the carbonization time is 3 hours, so as to remove volatiles in the dry material, reduce the residual organic matter, and obtain the above-mentioned precursor with a stable structure; S4, pulverizing: adding the precursor to a high-pressure pulverizer, and performing a pulverizing operation to obtain a pulverized material with a D50 of 7-8 μm, wherein the pulverizing method is air flow pulverization, which has the advantage of uniform particle size distribution of the pulverized material; S5, pore-forming by alkali treatment: adding the crushed material to a mixed alkali solution, stirring, filtering, and drying in sequence to obtain a pore-forming material, wherein the mixed alkali solution is a deionized water mixture of potassium hydroxide and sodium hydroxide, and the OH content of the mixed alkali solution is 0.0447 W / m. - The concentration is 1.0 mol / L, and the weight ratio of the mixed alkali solution to the crushed material is 2:1; S6, pickling and drying: adding the pore-forming material to the acid solution, stirring, filtering and drying in sequence to obtain a pure material, wherein the acid solution is a mixture of hypochlorous acid and hydrofluoric acid, the stirring and pickling time is 3.5 hours, the pH value of the filtered filter material is 3.0, the ash content of the pure material is less than 0.5%, and the moisture content is ≤0.22%: S7, resin coating: adding the pure material and the resin coating material into the coating machine, heating and stirring in an inert gas atmosphere to obtain a modified hard carbon material, wherein the resin coating material is a phenolic resin, and the weight ratio of the resin coating material to the pure material is 0.2:1, and the coating operation is carried out in a staged heating mode, that is, firstly heating to 250°C within 50 minutes and maintaining for 3 minutes, then heating to 400°C within 75 minutes and maintaining for 3 minutes, then heating to 500°C within 50 minutes and maintaining for 3 hours, during which the stirring and coating operation is continuously carried out, and finally the stirring operation is turned off and cooled to room temperature to obtain the modified hard carbon material; S8, second carbonization: adding the modified hard carbon material into a high temperature furnace, and performing carbonization operation in an inert gas atmosphere to obtain a secondary carbonized material, wherein the carbonization temperature is 900° C., the time is 25 h, and the heating rate of the carbonization process is ≤5° C. / min; S9, screening: adding the secondary carbonized material to the vibrating screen and performing screening, the screened material is the final novel bamboo-based hard carbon material, wherein the mesh number of the vibrating screen is 600 meshes, and the secondary carbonized material is demagnetized before being added to the vibrating screen.
[0028] Example 2 A novel method for preparing bamboo-based hard carbon material comprises the following steps in sequence: S1, crushing: adding bamboo material into a crusher, and crushing the material to obtain coarse material with a particle size of 1-3 mm, wherein the bamboo material is selected from moso bamboo grown for more than 3 years; S2, drying: adding the coarse material into a dryer, performing a heating and drying operation to obtain a dry material, wherein the heating and drying operation is performed at a temperature of 265° C. for 2 hours, so as to improve the efficiency of the subsequent carbonization process; S3, first carbonization: adding the dry material into a high temperature furnace, and performing a carbonization operation in an inert gas atmosphere to obtain a precursor, wherein the carbonization operation temperature is 480° C., the heating rate is 3.5-4.0° C. / min, and the carbonization time is 3 hours, so as to remove volatiles in the dry material, reduce the residual organic matter, and obtain the above-mentioned precursor with a stable structure; S4, pulverizing: adding the precursor to a high-pressure pulverizer, and performing a pulverizing operation to obtain a pulverized material with a D50 of 7-8 μm, wherein the pulverizing method is air flow pulverization, which has the advantage of uniform particle size distribution of the pulverized material; S5, pore-forming by alkali treatment: adding the crushed material to a mixed alkali solution, stirring, filtering, and drying in sequence to obtain a pore-forming material, wherein the mixed alkali solution is a deionized water mixture of potassium hydroxide and sodium hydroxide, and the OH content of the mixed alkali solution is 0.0447 W / m. -The concentration is 1.5 mol / L, and the weight ratio of the mixed alkali solution to the crushed material is 3:1; S6, pickling and drying: adding the pore-forming material to the acid solution, stirring, filtering and drying in sequence to obtain a pure material, wherein the acid solution is a mixture of hypochlorous acid and hydrofluoric acid, the stirring and pickling time is 5 hours, the pH value of the filtered filter material is 2.5, the ash content of the pure material is less than 0.5%, and the moisture content is ≤ 0.22%: S7, resin coating: adding the pure material and the resin coating material into the coating machine, heating and stirring in an inert gas atmosphere to obtain a modified hard carbon material, wherein the resin coating material is an epoxy resin, and the weight ratio of the resin coating material to the pure material is 0.25:1, and the coating operation is carried out in a staged heating mode, that is, firstly heating to 250°C within 50 minutes and maintaining for 3 minutes, then heating to 400°C within 75 minutes and maintaining for 3 minutes, then heating to 500°C within 50 minutes and maintaining for 3 hours, during which the stirring and coating operation is continuously carried out, and finally the stirring operation is turned off and cooled to room temperature to obtain the modified hard carbon material; S8, second carbonization: adding the modified hard carbon material into a high temperature furnace, and performing carbonization operation in an inert gas atmosphere to obtain a secondary carbonized material, wherein the carbonization temperature is 850° C., the time is 28 hours, and the heating rate of the carbonization process is ≤5° C. / min; S9, screening: adding the secondary carbonized material to the vibrating screen and performing screening, the screened material is the final novel bamboo-based hard carbon material, wherein the mesh number of the vibrating screen is 600 meshes, and the secondary carbonized material is demagnetized before being added to the vibrating screen.
[0029] Example 3 A novel method for preparing bamboo-based hard carbon material comprises the following steps in sequence: S1, crushing: adding bamboo material into a crusher, and crushing the material to obtain coarse material with a particle size of 1-3 mm, wherein the bamboo material is selected from moso bamboo grown for more than 3 years; S2, drying: adding the coarse material into a dryer, performing a heating and drying operation to obtain a dry material, wherein the heating and drying operation is performed at a temperature of 300° C. for 2 hours, so as to improve the efficiency of the subsequent carbonization process; S3, first carbonization: adding the dry material into a high temperature furnace, and performing a carbonization operation in an inert gas atmosphere to obtain a precursor, wherein the carbonization operation temperature is 420° C., the heating rate is 2.0-4.0° C. / min, and the carbonization time is 3 hours, so as to remove volatiles in the dry material, reduce the residual organic matter, and obtain the above-mentioned precursor with a stable structure; S4, pulverizing: adding the precursor to a high-pressure pulverizer, and performing a pulverizing operation to obtain a pulverized material with a D50 of 7-8 μm, wherein the pulverizing method is air flow pulverization, which has the advantage of uniform particle size distribution of the pulverized material; S5, pore-forming by alkali treatment: adding the crushed material to a mixed alkali solution, stirring, filtering, and drying in sequence to obtain a pore-forming material, wherein the mixed alkali solution is a deionized water mixture of potassium hydroxide and sodium hydroxide, and the OH content of the mixed alkali solution is 0.0447 W / m. - The concentration is 1.4 mol / L, and the weight ratio of the mixed alkali solution to the crushed material is 1.5:1; S6, pickling and drying: adding the pore-forming material to the acid solution, stirring, filtering and drying in sequence to obtain a pure material, wherein the acid solution is a mixture of hypochlorous acid and hydrofluoric acid, the stirring and pickling time is 4 hours, the pH value of the filtered filter material is 2.5, the ash content of the pure material is less than 0.5%, and the moisture content is ≤0.22%: S7, resin coating: adding the pure material and the resin coating material into the coating machine, heating and stirring in an inert gas atmosphere to obtain a modified hard carbon material, wherein the resin coating material is an epoxy resin, and the weight ratio of the resin coating material to the pure material is 0.22:1, and the coating operation is carried out in a staged heating mode, that is, firstly heating to 250°C within 50 minutes and maintaining for 3 minutes, then heating to 400°C within 75 minutes and maintaining for 3 minutes, then heating to 500°C within 50 minutes and maintaining for 3 hours, during which the stirring and coating operation is continuously carried out, and finally the stirring operation is turned off and cooled to room temperature to obtain the modified hard carbon material; S8, second carbonization: adding the modified hard carbon material into a high temperature furnace, and performing carbonization operation in an inert gas atmosphere to obtain a secondary carbonized material, wherein the carbonization temperature is 890° C., the time is 29 hours, and the heating rate of the carbonization process is ≤5° C. / min; S9, screening: adding the secondary carbonized material to the vibrating screen and performing screening, the screened material is the final novel bamboo-based hard carbon material, wherein the mesh number of the vibrating screen is 600 meshes, and the secondary carbonized material is demagnetized before being added to the vibrating screen.
[0030] Comparative Example 1 The preparation method in this comparative example is different from that in Example 1 in the following respects: S5. The alkali treatment pore-making operation is not carried out, and the crushed material is directly subjected to the acid washing and drying operation.
[0031] Comparative Example 2 The preparation method in this comparative example is different from that in Example 1 in only the following two points.
[0032] First: S5, the alkali treatment pore-making operation is not carried out, and the crushed material is directly subjected to the acid washing and drying operation; Second: S7, in the resin coating, potassium hydroxide as an activator is added together with the resin coating material, and the weight ratio of the two is 2:1.
[0033] Comparative Example 3 The preparation method in this comparative example is different from that in Example 1 in the following respects: S6: Pickling and drying operations are not performed, and the pore-forming material is directly subjected to resin coating operations.
[0034] Comparative Example 4 The preparation method in this comparative example is different from that in Example 1 in the following respects: S7. In the resin coating, the weight ratio of the resin coating material to the pure material is 1:1.
[0035] Sodium ion battery performance test The above 7 groups of hard carbon materials were used as negative electrodes, sodium metal oxide was used as positive electrodes, the active material was set to: PVDF: carbon black = 8:1, the electrolyte was sodium perchlorate NC-005 (1M NaClO4in PC=100 Vol% with 2%FEC), and the separator was glass fiber. They were assembled into button cells for testing (model 2032).
[0036] The hard carbon materials in the above three embodiments and four comparative examples were tested for performance five times respectively, and the average values were taken and recorded in the following table;
[0037] Test results analysis The sodium ion batteries corresponding to the hard carbon negative electrode materials in the first and third embodiments all have a large specific capacity and a high first coulombic efficiency, while the preparation method in comparative example 2 is a common method in the prior art, and the former has a greater performance improvement than the latter; Second, the performance of the sodium ion batteries corresponding to the hard carbon negative electrode materials in the four comparative examples has been degraded in different degrees and aspects compared with the three embodiments. This shows that the specific steps in the embodiments: alkaline treatment to form pores, acid washing and drying, and resin coating are all indispensable in achieving higher performance of the hard carbon negative electrode materials.
[0038] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various modifications can be made within the knowledge of ordinary technicians in the technical field without departing from the purpose of the present invention. These are all non-creative modifications and are protected by patent law as long as they are within the scope of the claims of the present invention.
Claims
1. A novel method for preparing bamboo-based hard carbon material, characterized in that The following steps are included in sequence: S1. Crushing: Add bamboo material into the crusher and perform crushing operation to obtain coarse material with a particle size of 1-3 mm; S2, drying: adding the coarse material into a dryer, performing heating and drying operations to obtain dry material; S3, first carbonization: adding the dry material into a high temperature furnace, and performing a carbonization operation in an inert gas atmosphere to obtain a precursor; S4, crushing: adding the precursor into a high-pressure crusher, and crushing the precursor to obtain a crushed material with a D50 of 7-8 μm; S5, pore-forming by alkali treatment: adding the crushed material to the mixed alkali solution, stirring, filtering, and drying in sequence to obtain a pore-forming material; S6, acid washing and drying: adding the pore-forming material to the acid solution, stirring, filtering, and drying in sequence to obtain a pure material; S7, resin coating: adding the pure material and the resin coated material into a coating machine, performing heating and stirring operations in an inert gas atmosphere to obtain a modified hard carbon material; S8, second carbonization: adding the modified hard carbon material into a high temperature furnace, and performing a carbonization operation in an inert gas atmosphere to obtain a secondary carbonized material; S9, screening: adding the secondary carbonized material to a vibrating screen and performing screening treatment, and the screened material is the final novel bamboo-based hard carbon material.
2. The method for preparing a novel bamboo-based hard carbon material according to claim 1, characterized in that: In S5, the mixed alkaline solution is a deionized water mixture of potassium hydroxide and sodium hydroxide. - The concentration is 1.0-1.5 mol / L, and the weight ratio of the mixed alkali solution to the crushed material is (1.5-3.0):
1.
3. The method for preparing a novel bamboo-based hard carbon material according to claim 1, characterized in that: In S7, the resin coating material is any one of phenolic resin and epoxy resin, the weight ratio of the resin coating material to the pure material is (0.20-0.25):1, and the temperature of the heating and stirring operation is 250-500°C.
4. The method for preparing a novel bamboo-based hard carbon material according to claim 1, characterized in that: In S2, the temperature of the heating and drying operation is 200-300°C and the time is 1-2h.
5. The method for preparing a novel bamboo-based hard carbon material according to claim 1, characterized in that: In S3, the temperature of the first carbonization operation is 400-500°C, the heating rate is 2-5°C / min, and the carbonization time is 2-3h.
6. The method for preparing a novel bamboo-based hard carbon material according to claim 1, characterized in that: In S6, the acid solution is a mixture of hypochlorous acid and hydrofluoric acid, the stirring and acid washing time is ≥3h, and the pH value of the filter material after filtration is ≤3.
7. The method for preparing a novel bamboo-based hard carbon material according to claim 1, characterized in that: The drying operation in S6 is continued until the moisture content of the dried material is ≤0.22%.
8. The method for preparing a novel bamboo-based hard carbon material according to claim 1, characterized in that: In S8, the temperature of the second carbonization operation is 850-900°C and the time is 25-30h.
9. The method for preparing a novel bamboo-based hard carbon material according to claim 1, characterized in that: In S9, the mesh size of the vibrating screen is ≥ 600 meshes.
10. The method for preparing a novel bamboo-based hard carbon material according to claim 1, characterized in that: In S9, the secondary carbonized material is first demagnetized before being added to the vibrating screen.
Citation Information
Patent Citations
Method for preparing coal-based hard carbon negative electrode material through alkali treatment modification and application
CN115650228A
Preparation method and application of biomass hard carbon sodium ion battery negative electrode material
CN117246997A
Silicon-doped sodium ion battery hard carbon negative electrode material and preparation method thereof
CN118507722A
Sodium-ion battery negative electrode biomass hard carbon material, preparation method and sodium-ion battery
CN118529711A
The method of Preparing Porous Carbon using Coal-Tar Materials
KR101835715B1
Cited By
Method for preparing hard carbon based on biomass industrial waste and application
CN121020546A
